2006
DOI: 10.1007/s00264-006-0205-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment results of pathological fractures of the long bones: a retrospective analysis of 88 patients

Abstract: Due to the advances in oncological therapy, the life expectancy of patients with malignant tumours and the incidence of pathological fractures have increased over the last decades. Pathological fractures of the long bones are common complications of metastatic disease; however, the outcome of different surgical techniques for the treatment of these fractures has not been clearly defined. The aim of this study was to evaluate differences in patient's survival and postoperative complications after the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 29 publications
0
36
0
1
Order By: Relevance
“…Patients undergoing fixation of pathological fractures benefit from these procedures in terms of mobility and reduction in local pain [18]. Prevention of fracture by prophylactic fixation offers both technical and patient related benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing fixation of pathological fractures benefit from these procedures in terms of mobility and reduction in local pain [18]. Prevention of fracture by prophylactic fixation offers both technical and patient related benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment options for pathological fracture in malignant bone sarcomas range from reconstructive surgery to amputation [20]. Limb salvage has become a popular alternative to amputation for the treatment of malignant bone tumours and can improve functional outcome [23][24][25]. Within this setting it is of pivotal interest whether limb salvage has any effect on the long-term survival of patients, and few studies have specifically compared the outcome of limb salvage versus amputation [1,2,5,13,16,22,27].…”
Section: Introductionmentioning
confidence: 99%
“…Implant failure rates regarding proximal femur pathological fractures vary vastly in different literatures, ranging from 0-23% (5,12,28,29). A study by Manoso et al (28) reported the most favorable results that no infections, dislocations or reoperations were observed in a 6-year retrospective study with 13 cancer patients with proximal femur metastasis treated with proximal femur replacement.…”
Section: Msts-93 Score ----------------------------------------------mentioning
confidence: 99%
“…Surgical modalities are widely regarded as effective, most of which include endoprosthetic reconstruction (EPR) (1,3,7,8,(10)(11)(12)(13), intramedullary nailing (IMN) and open reduction-internal fixation (4,5,9,10,14). Although these surgical strategies are usually palliative, consensus of the optimal surgical procedure has not been reached.…”
Section: Introductionmentioning
confidence: 99%